ANALISIS KEMAMPUAN PEMECAHAN MASALAH DAN KEMAMPUAN PENALARAN MATEMATIS SISWA MATERI EKSPONEN DAN LOGARITMA - Sri Satriani (Delta: Jurnal Ilmiah Pendidikan Matematika, 2020)
AbstractThe purpose of this study aims to determine the problem solving ability and reasoning ability of students in understanding exponential and logarithms material. The type of research in this study is qualitative research. To express this ability used a mathematical ability test instrument and conduct interviews. The subjects of this study were 30 students of class X MIPA of SMA Negeri 7 Mallawa, which were then chosen by 1 person each for low, medium, and high ability levels. The data obtained were analyzed using descriptive statistics and interviews were analyzed using the Miles and Huberman models. The results showed that the problem solving ability of students with low ability was in the students' inability to understand the problem and the lack of understanding of the concept of logarithmic concepts and exponents, for students who were capable of being there were still improper completion steps. As for students who are highly capable have been able to identified the elements present in the problem, able to understand the problem and solved the given problem. Where as the mathematical reasoning ability of students with low ability is very lacking because they are unable to complete the answers and cannot write the characteristics of logarithms and exponents, while for students with medium and high ability the reasoning ability are quite well proven by their ability to place the characteristics of logarithms and exponents correctly and  they are able to used the properties of exponents and logarithms in solving problems properly.problem solving ability, reasoning ability, logarithms exponential